A Semiotic analysis of Malaysian car tv advertisements : The proton's of 2003-2014 - Chou En-I (2017)
Today people live in a visually intensive society with a world of spectacular and exciting images surrounding them on a daily basis. Advertising is one of the marketing strategies to promote products to consumers. Perusahaan Otomobil Nasional Berhad (PROTON), Malaysian automobile company, was a company incorporated in 1983. In the midst of fierce competitions in the industry made up of automobiles, the management of businesses and strategies in marketing is important but the advertisements are essential to its progress. This research would be helpful for PROTON to find out which style of advertising is most effective on PROTON sales, which they can then adopt to achieve the best results. This paper examines automotive 1V advertisements in Malaysia to determine how advertisers achieved their primary goal of convincing the audience using semiotics. Secondly, how the advertisements encoded national identity and cultural values are also discussed. Semiotics theory can be used as references for the Malaysian car advertising development. This research would be helpful for PROTON to find out which style of advertising is most effective on PROTON sales, which they can then adopt to achieve the best results. The method of research is semi-structured interviews with 55 respondents in the urban and rural areas. 45 respondents were from urban areas such as Sabah, Sarawak, Johar, Kuala Lumpur and Penang. The remaining 15 respondents were from rural Kampung Bambangan, Inanam and Kampung Pompod, Kota Belud. The research found that the majority of Malaysians had been represented in the study to respond to advertising that determined their purchases. Findings of the thesis showed that there is a vast gap in what the audience wants to see in an advertisement and what the advertisers showed causing sales to be a standstill. When the gap is close in term of expectation and performance, the response towards the advertisements were positive. The is a need to match the expectations of the audience by putting out advertisements that matched their expectation so as to positively increase sales and purchases.